Chinese looks : fashion, performance, race - Metzger, Sean, 1973- (Indiana University Press, 2014)
From yellow-face performance in the 19th century to Jackie Chan in the 21st, Chinese Looks examines articles of clothing and modes of adornment as a window on how American views of China have changed in the past 150 years. Sean Metzger provides a cultural history of three iconic objects in theatrical and cinematic performance: the queue, or man''s hair braid; the woman''s suit known as the qipao; and the Mao suit. Each object emerges at a pivotal moment in US-China relations, indexing shifts in the balance of power between the two nations. Metzger shows how aesthetics, gender, politics, econom.